How can we scale low-emission food systems? A six-step approach - Yomayuza Herrera, Karoll Valentina; Ramirez Perez, Elizabeth; Amahnui, George Amenchwi (2025)
The global food system contributes around one-third of human-made GHG emissions. Transforming it requires more than just new technologies—it demands supportive policies, incentives, and strategies to overcome complex barriers. This video introduces a Six-Step Approach to scaling innovations that reduce emissions while supporting Sustainable Development Goals (SDGs). Learn how to identify emission drivers, align priorities, unlock adoption, and measure impact—featuring a real-world case from the Colombian Amazon. 📍 Includes insights on silvopastoral systems, finance, and policy integration.